Kufundziswa kwetilwimi taseNingizimu Afrika ngekusebentisa bucwepheshe - Mkhwanazi, Malilensha Cecilia (Journal for Language Teaching, 2024)
ENGLISH TITLE: Teaching South African languages through technology African languages are behind, especially with regards to terminology in education, and entering the digital environment. This research considers the teaching of South African languages through technology and its presence in the digital space. What can we do in this regard? First, it is important that we have to educate our teachers on how to use technology in teaching South African languages. The paper explores the potential in the use of technology and occupying the digital space available. It examines how South African languages can be integrated with other subjects like coding and robotics. In other words, teaching African languages through technology can produce learners who will be empowered with 21st-century skills and be able to use the information that will be digitally relevant. The study adopted Actor Network Theory (ANT) to direct its activities. This framework gives credit to any being or factor, irrespective of its nature, human, or non-human. ANT is a theory of the progressive constitution of a network in which both human and non-human actors assume identities. The data and information that were generated through participatory action research, a desktop review, a literature review and textual analysis were analysed using critical discourse analysis (CDA). This was used to show how discourse structures reproduce, legitimize, question, or perform power and dominance relations in society. Also, CDA is an analytical research approach that analyses speech critically. A person or group of dominant tendencies review critical discourse analysis trying to explain a social reality and have a specific goal in mind. Findings suggest that collaboration with all stakeholders in digitising and teaching through technology is possible. We also look at the contribution of the Web in promoting the use and status of African languages. Participation in sharing and producing knowledge through the Web can play a key role in the economic, social and educational development of Africa. The research will be of interest for educators, especially in higher education institutions, in teaching African languages through technology. It is important to digitise all our African languages, especially Siswati. These languages can develop and then be found in the digital space in such a way that they can be used or spoken internationally. Another opportunity can be found in the enhancement of the national corpora, the use of other software and open-source platforms like Wikipedia, WordNet, and also the use of technology to teach the South African languages. African languages can indeed be satisfactorily developed in these respects. Lugcogco Tilwimi tase-Afrika betatiwa njengetilwimi letisemuva ngetintfo letiningi, lokunye kwato kungabi nemagama (terminology) kulomkhakha wetemfundvo tibuye futsi tingabikhona etindzaweni tedijithali. Inhloso yalolucwaningo kubuka kufundzisa kwetilwimi tase-Africa ngebucwepheshe besimanje kanye nekubakhona kwato etindzaweni tedijithali. Umbuto longatibuta wona kutsi, Yini lekumele yentiwe kute tilwimi tetfu tase-Afrika tifundziswe nato ngebucwepheshe besimanje? Singatisabalalisa njani etindzaweni tedijithali? Ngalemibuto lemibili kubalulekile kutsi bothishela bafundziswe kusebentisa bucwepheshe besimanje ekufundziseni tilwimi taseAfrika. Leliphepha lihlose kuveta kutsi Tilwimi tase-Afrika tingafundziswa tisebentisa bucwepheshe besimanje kantsi futsi tibuye lisatjalaliswe etindzaweni tedijithali. Lokunye lelikubukile kutsi tilwimi tase-Afrika tingafundziswa ngekuhlanganisa letinye tifundvo letifana nabo-khodingi kanye nerobothiksi. Ngalamaye emavi tifundvo letikhicita bantfwana lebatakwati kucabanga, kucatulula tinkinga nekutfola tisombululo letinemcondvo tingafundziswa etilwimini taseAfrika. Lolucwaningo lusebentise indlela yekucwaninga ye khwalithethivu lephindze isebentise indlela yekusampula lebuka injongo (purposive). Lolucwaningo lincike kakhulu ekubukisiseni lwendlela yeluhlolo lwedeksithophu(Desktop), luhlolo lwetincwadzi (document analysis). Lelucwaningo lubuke kusetjetiswa kwe-Actor Network Theory lokuyi mfundziso-njulalwati (theoretical framework) lokungilo lolukwati kusebentisana naleminye imibhalo. Kuhlatiywa kwalokutfolakele (data analysis) lutawusebentisa Indlelanchubo yekwehlukanisa ngetingcikitsi. Kufaka ligalelo: Lolucwaningo lungaba lusito kubafundzisi, ikakhulukati etikhungweni temfundvo lephakeme ekufundziseni tilwimi tase-Afrika ngekusebentisa itheknoloji kanye netilwimi tase-Afrika uma selutfolakala, selukhulunywa ngaphesheya kwetilwandle.